Growing up in ethnic enclaves: language proficiency and educational attainment of immigrant children - Alexander M. Danzer; Carsten Feuerbaum; Marc Piopiunik; Ludger Woessmann (Journal of Population Economics, 2022)
Does the regional concentration of immigrants of the same ethnicity affect immigrant children's acquisition of host country language skills and educational attainment? We exploit the concentration of five ethnic groups in 1985 emanating from the exogenous placement of guest workers across German regions during the 1960s and 1970s. Results from a model with region and ethnicity fixed effects indicate that exposure to a higher own ethnic concentration impairs immigrant children's host country language proficiency and increases school dropout. A key mediating factor for the detrimental language effect is parents' lower speaking proficiency in the host country language, whereas inter-ethnic contacts with natives and economic conditions do not play a role in language proficiency or educational attainment.
Keywords: J15; I20; R23; J61; 330; Immigrant children; Ethnic concentration; Language; Education; Guest workers